The Effect of Single Leg Hop Exercise on Leg Muscle Power in Men's Low Kick Right Low Kick Wushu Sanda Athletes, Kediri City in 2022 - Thasania Charla; Mokhammad Firdaus; M. Akbar Husein Alsabbah (CV. Nusantara Sporta, 2023)
The discovery of problems, not all of them are used as problems in this study, therefore from the problem